Predictive value of the serum homocysteine-to-albumin ratio for major adverse cardiovascular events after acute myocardial infarction: a retrospective cohort study - Wang, Jiaping; Zhou, Jianling; Wang, Na; Fu, Meili; Song, Ziwen; Hu, Ming; Wu, Huiyi; Sun, Runfeng (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAcute myocardial infarction (AMI) remains a major global health burden, with major adverse cardiovascular events (MACE) significantly affecting long-term prognosis. Although the Global Registry of Acute Coronary Events (GRACE) score is widely used for risk stratification, its complexity limits its clinical utility, especially in resource-limited settings. The serum homocysteine-to-albumin ratio (HAR) is a novel biomarker that combines oxidative stress and inflammatory processes, both of which play key roles in cardiovascular pathophysiology. This study aimed to assess the prognostic significance of HAR for MACE in AMI patients.MethodsA retrospective cohort study was conducted, including 421 AMI patients admitted to Donghai Hospital from January 2022 to December 2023. Clinical and laboratory data, including homocysteine (Hcy), albumin (Alb), and HAR, were collected. The primary outcome was MACE, defined as cardiovascular mortality, non-fatal myocardial infarction, heart failure, recurrent revascularization, stroke, and severe arrhythmias. Multivariable Cox regression analysis was performed to identify independent predictors of MACE. The predictive performance of HAR was assessed using receiver operating characteristic (ROC) curve analysis and compared with Hcy, Alb, and the GRACE score.ResultsDuring the 12-month follow-up period, 105 patients (24.9%) experienced MACE. The MACE group had significantly higher Hcy levels (15.7 ± 3.4 vs. 12.6 ± 3.1 μmol/L, P < 0.001) and lower Alb levels (34.2 ± 3.9 vs. 38.5 ± 4.2 g/L, P < 0.001). HAR was independently associated with MACE (HR = 1.41, 95% CI: 1.20–1.65, P < 0.001). ROC analysis demonstrated that HAR (AUC = 0.80) outperformed Hcy (AUC = 0.66) and Alb (AUC = 0.73) in predicting MACE, with predictive accuracy comparable to the GRACE score (AUC = 0.82).ConclusionsHAR is a strong and independent predictor of MACE in AMI patients. Given its simplicity, cost-effectiveness, and availability, HAR may serve as a valuable biomarker for cardiovascular risk stratification, especially in resource-limited settings. Further prospective studies are warranted to validate these findings and explore potential clinical applications.